Nanotechnology applications for solar energy systems - Sheikholeslami, Mohsen, 1988- (John Wiley & Sons, Inc., 2023)
Nanotechnology Applications for Solar Energy Systems Understand the latest developments in solar nanotechnology with this comprehensive guide Solar energy has never seemed a more critical component of humanity's future. As global researchers and industries work to develop sustainable technologies and energy sources worldwide, the need to increase efficiency and decrease costs becomes paramount. Nanotechnology has the potential to play a considerable role in meeting these challenges, leading to the development of solar energy systems that overcome the limitations of existing technologies. Nanotechnology Applications for Solar Energy Systems is a comprehensive guide to the latest technological advancements and applications of nanotechnology in the field of solar energy. It analyzes nanotechnology applications across a full range of solar energy systems, reviewing feasible technological advancements for enhanced performance of solar energy devices, and discussing emerging nanomaterials such as graphene and graphene derivatives. Nanotechnology Applications for Solar Energy Systems readers will also find: Detailed treatment of nanotechnology applications in systems including solar concentrating collectors, linear Fresnel reflectors, parabolic trough collectors, and more Coverage of methods to enhance the performance of solar energy devices including solar ponds and solar steam generators A comprehensive review of nanomaterials classification and the properties of nanomaterials in heat transfer and efficiency enhancement Nanotechnology Applications for Solar Energy Systems is critical for researchers in fields related to solar energy, engineers and industry professionals developing solar technology, and academics working in related fields such as chemistry, physics, materials science, and electrical engineering.